Clinical and Epidemiological Features and Antimicrobial Susceptibility Patterns of Chryseobacterium Species: A Scoping Review - Chienhsiu Huang (Medicina)
Background and Objectives: Infections with Chryseobacterium species are rare, and the susceptibility patterns of these species to antimicrobial agents are unclear. Therefore, the aim of this study was to explore the clinical and epidemiological features and antimicrobial susceptibility patterns of Chryseobacterium species by reviewing previous research on the antibiograms of Chryseobacterium species and the illnesses caused by Chryseobacterium species. Materials and Methods: A comprehensive search of the PubMed and Web of Science databases was conducted for all studies that investigated antimicrobial susceptibility patterns of Chryseobacterium species published between January 1990 and February 2025. An extensive review of the infection incidences, isolation sites, clinical characteristics, and antimicrobial susceptibility patterns for infections caused by Chryseobacterium species was performed. Results: Several studies have revealed that the incidence of Chryseobacterium species infections is increasing, particularly in patients with comorbid conditions, mainly cardiovascular disease, diabetes mellitus, and malignancy. Most patients were elderly individuals, and most related illnesses were acquired in hospitals. The number of patients who received inappropriate antimicrobial therapy outnumbered the number of those who died. Antibiotics had little effect on Chryseobacterium species infection outcomes. Sixteen studies were included in the current scoping review. The susceptibility rates of Chryseobacterium indologenes to piperacillin/tazobactam (2.9–100%), ciprofloxacin (4.34–85%), levofloxacin (8.69–100%), trimethoprim/sulfamethoxazole (33.3–100%), imipenem (0–33.3%), meropenem (0–38.8%), minocycline (30.4–100%), ceftazidime (0–100%), and cefepime (0–100%) varied. The susceptibility rates of Chryseobacterium gleum to piperacillin/tazobactam (0–33%), ciprofloxacin (21.4–40%), levofloxacin (59.5%), trimethoprim/sulfamethoxazole (57.1–93.3%), imipenem (0–2.4%), meropenem (0%), minocycline (83.3–100%), ceftazidime (0–23.8%), and cefepime (0–19.0%) varied. Conclusions: Morbidity and mortality due to the increasing incidence of Chryseobacterium species infections have considerably increased. Underlying immunological defenses and other clinical factors may influence the prognosis of Chryseobacterium species infection. Rather than bacterial virulence characteristics, host factors mostly affect patient outcomes. Most isolates of Chryseobacterium indologenes are susceptible to minocycline and trimethoprim/sulfamethoxazole. For the treatment of these infections, professional knowledge and therapeutic expertise must be integrated.